Calidad de vida en niños de 8 a 12 años de edad que practican actividad física o deporte en la institución académica Berakah Academy School en la ciudad de Cartagena - Salcedo Diaz Doris María (Universidad Antonio Nariño, 2025)
This work aims to describe the quality of life in children from 8 to 12 years of age who practice physical activity or sports at the academic institution Berakah Academy School in the city of Cartagena. The research had a quantitative methodological design in order to recognize the level of quality of life by domains in the selected sample of students; For this purpose, the health and well-being questionnaire of children and adolescents from 8 to 18 years old KIDSCREEN-27 developed for the KIDSCREEN Project and designed by the European Commission in 2001, validated in Colombia by Quintero (2011), was applied; Descriptive statistics are used to analyze the information.